KEWENANGAN LEMBAGA-LEMBAGA NEGARA DALAM MEMUTUS DAN MENAFSIRKAN UUD SETELAH AMANDEMEN KEEMPAT UNDANG-UNDANG DASAR 1945 - Mukhlis, Mukhlis (Syiar Hukum, 2011)
The Amanded of UUD 1945 changed basically the structure and State institutional. the change of  the structure State institutional that is, was formed several of the new State institutionals, among them the Yudisial Commission (KY), the Constitutional  Court (MK) and the Council of Representative of the Area (DPD). The UUD 1945 amanded unclear defined the State institutional, that is caused the inter-institutional authority dispute . Who right to  interpreted the State institutional and what institution  that were said as the State institution  according to UUD 1945 fourth amanded  . The Institution that the Right to interpreted UUD 1945 is  the Constitutional Court. The State institutional that were meant in UUD 1945 is Peoples Consultative Assembly, the Peoples Representative Council, DPD, President, The ministry  of the State , BPK, , DPRD, the Commission of general election  (KPU), the Yudisial Commission, , the central bank, Republic of Indonesia Army, Republic of Indonesia State Police, and the Council of  President consideration  . The constitutional court had the authority to settle of   the inter-institutional authority dispute of the country that his authority was given by UUD 1945.